Alginate based nanoparticles as a carrier matrix for the delivery of calixarene derivative as Pharmaceutical compound (Funded Work) - ABHISHEK SAXENA; NEETA BHAGAT; 2KUMAR; LOVNISH SIYAL; BENU KUMAR; RACHANA SAHNEY (International Journal of Pharma and Bio Sciences, 2017)
Modern medicines are in urgent need of hyphenating new therapeutics, which can act as antimicrobial agent. Calixarenes are versatile macromolecules which can serve as a platform for the design and development of biologically active therapeutics. But the presence of aromatic ring structure in the calixarenes skeleton renders it hydrophobic which requires a hydrophilic carrier to reach the target cell efficiently for drug action. The present work is a comparative study of antimicrobial activity of sodium salt of p-sulfonato-calix-4-arene (calixarene derivative) in aqueous solution (phosphate buffer saline) and encapsulated in hydrophilic nanocarrier – alginate nanogel cross-linked with Ca+2/Ba+2. The alginate nanogels were characterized with respect to their size, encapsulation efficiency and their drug release profiles. Antimicrobial activity of p-sulfonato-calix-4-arene and alginate nanogels loaded with the p-sulfonato-calix-4-arene was determined by disc diffusion method and colony forming unit (CFU) method against drug resistant strain of Escherichia coli (MTCC 443). The experimental results suggest that the encapsulated calixarene derivative in hydrophilic calcium alginate nanogels is potentially best candidate against E.coli strain at much lower concentration than the free calixarene derivative soluble in phosphate buffer saline (PBS).